Modulating grapevine performance and hormonal dynamics under summer stress by the synergistic effects of kaolin and silicon - Pereira, Sandra; Monteiro, Ana; Baltazar, Miguel; Maia, Carolina; Pereira, Sara; Oliveira, Manuel João; Pádua, Luís; Gonçalves, Igor; Soares, Bruno; Branco, Zélia; Moura, Renata; Balfagón, Damián; et al. (Frontiers in Plant Science, 2025)
IntroductionClimate change is intensifying heat and drought stress in viticulture, negatively impacting yield and grape quality. High temperatures accelerate sugar accumulation and reduce organic acids, disrupting wine balance. Drought also lowers grapevine resilience by reducing stomatal conductance and photosynthetic efficiency, highlighting the need for sustainable strategies. This study evaluated the effects of foliar applications of kaolin (Kl) and silicon (Si) mixtures on grapevine physiology and fruit quality under summer stress. MethodsThe experiment was conducted over two seasons (2023–2024) in a commercial vineyard (Quinta de Ventozelo, Douro Region) using the Touriga Franca variety. Treatments included a control and four formulations (MiKS 1 to 4), all with 2% Kl and Si ranging from 2% to 8%. Physiological measurements included gas exchange, chlorophyll a fluorescence, and leaf water potential. Biochemical analyses assessed pigments, sugars, proteins, phenols, flavonoids, ortho-diphenols, and leaf anatomy. Hormonal profiling (abscisic acid (ABA), indole-3-acetic acid (IAA), jasmonic acid (JA), and salicylic acid (SA)) was also performed. ResultsSi and Kl treatments, particularly MiKS 3 and MiKS 4, significantly enhanced gas exchange parameters, water potential, and chlorophyll fluorescence under high-stress conditions. These treatments also increased chlorophyll, carotenoids, cuticular waxes, and cuticle thickness, contributing to improved plant vitality and stress resilience. Secondary metabolites such as ortho-diphenols were also enhanced. Hormonal profiling showed increased ABA and JA and decreased IAA and SA, suggesting strengthened stress signalling and defence responses. DiscussionOverall, Si and Kl mixtures effectively mitigated summer stress, improving grapevine physiological, biochemical, and anatomical responses under challenging climate conditions.